Entre o rio e o mar : educação ambiental para o fortalecimento da comunidade pesqueira do Mosqueiro - Aracaju/SE - Leite, Mirsa Mara Barreto Xavier (2007)
The Community of Mosqueiro is located at the extreme south of Aracaju city. According to the macro zoning carried out by the Secretary of Planning of Sergipe´s capital, it covers the Urban Growth Zone and has as its limits: the Atlantic Ocean, in the east, Canal Santa Maria (the Santa Maria Canal), in the west and the Vaza Barris River, in the south and southwest. The community has approximately 4.091 inhabitants and a relation of dependence on natural resources established more than a century ago, according to the local residents. As far as 1960, the accesses between Aracaju and Mosqueiro were restricted, as a result, many fishermen had to move on foot, on horseback or sailing in order to commercialize their products in the markets of Aracaju. During the decade of 1980, with the building of Rodovia dos Náufragos (Náufragos Road), the relations with Aracaju became more intense and people who lived in the capital started to frequent the community as holidaymakers, purchasing pieces of land and building houses. Some of these houses are permanent dwelling ones at present. This process has taken higher proportions year by year because of many factors and among them, stands the real estate speculation. As a consequence, the local community has been suffering strong influences, resulting in changes in the territorial, spacial, sociocultural, economic and environmental characteristics and setting off a deterritorialization process. Faced with the environmental complexity, it is necessary the contribution of the several fields of science in order to reach a wider and integrated view of the environmental questions (GOMIDE and SERRÃO, 2004). In this sense, the Environmental Education actions are presented in this research with the objective of contributing to the construction of proposals which imply the respect to biodiversity and cultural diversity, the incentive for solidarity, equality, the respect to traditional knowledge expressed in a community way of life. The methodology used consists in the application of participative research carried out by means of discursive and constructive workshops with the community social actors involvement. The educational process helps in the formation of new social actors capable of leading the transition to a democratic and sustainable future (LEFF, 2001, p.246).